Praktik Jual Beli Jizaf Pada Benih Padi Siap Tanam - Rumuzi, Moh.; Rahmawati, Rita; Inayati, Anindya Aryu (el hisbah Journal of Islamic Economic Law, 2022)
The sale and purchase of jizaf on ready-to-plant rice seeds, is a buying and selling practice where farmers sell ready-to-plant rice seeds by hand and tie them together. In this sale and purchase there is no clarity in size, and the measurement is only based on the grip of the hand, whereas in essence the size of each person's palm is different, some are large, some are small. In addition, the strength of the grip affects the content of the rice seeds, so there is no uniformity in the quantity of the dose in this sale and purchase. This type of research is a field research with a qualitative approach. Sources of data in the form of primary data obtained by observation and interviews with sellers and buyers, and secondary data sources obtained by documentation techniques. The data were analyzed using interactive model qualitative data analysis techniques. The results of the study concluded, the sale and purchase of ready-to-plant rice seeds in Lebo Village was in accordance with the pillars and terms of buying and selling by means of jizaf. Another factor in the permissibility of this buying and selling is that there is a great benefit in it, the benefit in terms of doing muamalah to help each other. This buying and selling practice is a habit of the local community ('urf), urf in this sale and purchase is a valid urf and does not conflict with Islamic teachings and can be used as a legal basis.